Estimated dead space fraction and the ventilatory ratio are associated with mortality in early ARDS - Luis Morales-Quinteros (2020)
© 2019, The Author(s). Background: Indirect indices for measuring impaired ventilation, such as the estimated dead space fraction and the ventilatory ratio, have been shown to be independently associated with an increased risk of mortality. This study aimed to compare various methods for dead space estimation and the ventilatory ratio in patients with acute respiratory distress syndrome (ARDS) and to determine their independent values for predicting death at day 30. The present study is a post hoc analysis of a prospective observational cohort study of ICUs of two tertiary care hospitals in the Netherlands. Results: Individual patient data from 940 ARDS patients were analyzed. Estimated dead space fraction and the ventilatory ratio at days 1 and 2 were significantly higher among non-survivors (p < 0.01). Dead space fraction calculation using the estimate from physiological variables [VD/VT phys] and the ventilatory ratio at day 2 showed independent association with mortality at 30 days (odds ratio 1.28 [95% CI 1.02–1.61], p < 0.03 and 1.20 [95% CI, 1.01–1.40], p < 0.03, respectively); whereas, the Harris–Benedict [VD/VT HB] and Penn State [VD/VT PS] estimations were not associated with mortality. The predicted validity of the estimated dead space fraction and the ventilatory ratio improved the baseline model based on PEEP, PaO2/FiO2, driving pressure and compliance of the respiratory system at day 2 (AUROCC 0.72 vs. 0.69, p < 0.05). Conclusions: Estimated methods for dead space calculation and the ventilatory ratio during the early course of ARDS are associated with mortality at day 30 and add statistically significant but limited improvement in the predictive accuracy to indices of oxygenation and respiratory system mechanics at the second day of mechanical ventilation.